2011
DOI: 10.1089/dna.2010.1128
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitously Expressed Hematological and Neurological Expressed 1 Downregulates Akt-Mediated GSK3β Signaling, and Its Knockdown Results in Deregulated G2/M Transition in Prostate Cells

Abstract: As the molecular mechanism of β-catenin deregulation is not well understood, and stabilized β-catenin is known to translocate into the nucleus and activate genes for proliferation, a novel regulatory factor, hematological and neurological expressed 1 (HN1), for Akt-GSK3β-β-catenin axis is reported here. In our studies, HN1 gene structure was characterized. HN1 expression was found to be epidermal growth factor-responsive in PC-3 cells, and protein expression was also upregulated in PC-3 and LNCaP but not in DU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 48 publications
6
50
0
Order By: Relevance
“…Further, activated Akt stabilizes β-catenin via inhibition of GSK3β [34] and directly phosphorylates β-catenin at S552, thereby promotes β-catenin transactivation [9]. Based on previous reports [35] and our findings reported here, we suggest that mimicking TNFα-mediated inflammation [20] in prostate cells results in a significant increase in pAkt (S473) , which consequently inhibits GSK3β kinase activity by increasing the phosphorylation from (S9) residue (Figure 1E). Furthermore, the decrease in β-catenin (S33) phosphorylation implies that either proteosomal degradation is activated and β-catenin (S33) is depleted by ubiquitination dependent proteosomal machinery, or there can be an increase in the stabilizing phosphorylation of β-catenin (S552) , which suppresses the S33 phosphorylation (Figure 1E) by enhanced Akt activity.…”
Section: Discussionsupporting
confidence: 78%
“…Further, activated Akt stabilizes β-catenin via inhibition of GSK3β [34] and directly phosphorylates β-catenin at S552, thereby promotes β-catenin transactivation [9]. Based on previous reports [35] and our findings reported here, we suggest that mimicking TNFα-mediated inflammation [20] in prostate cells results in a significant increase in pAkt (S473) , which consequently inhibits GSK3β kinase activity by increasing the phosphorylation from (S9) residue (Figure 1E). Furthermore, the decrease in β-catenin (S33) phosphorylation implies that either proteosomal degradation is activated and β-catenin (S33) is depleted by ubiquitination dependent proteosomal machinery, or there can be an increase in the stabilizing phosphorylation of β-catenin (S552) , which suppresses the S33 phosphorylation (Figure 1E) by enhanced Akt activity.…”
Section: Discussionsupporting
confidence: 78%
“…Here, our results demonstrated that frequently up-regulated miR-132 in breast cancer influence cancer cell behavior by targeting HN1. HN1 expression is high in various carcinomas, while low in benign tumors [13]. In general, HN1 is an interaction partner of the inactive GSK3b/b-catenin/APC complex, which promotes ubiquitin-dependent proteasomal degradation of b-catenin, and contributes to migration in prostate cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…HN1 was detected as an oncogene in some cancers. Depletion of HN1 in both melanoma and prostate cells results in cell cycle arresting-related proliferation suppression [12,13]. Moreover, in vitro and in vivo studies demonstrated that overexpressing HN1 promotes wound healing in prostate cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Side population analysis was performed according to the previous report [16]. Cell analysis using FACSCalibur cytometer (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%